The “Third letter” of Nicholas Rhabdas: An Autograph Easter Computus - Fabio Acerbi (Estudios Bizantinos, 2021)
The article presents an edition, a translation, a technical commentary, and a thematic word index of the Easter Computus authored by the Byzantine mathematichian Nicholas Artabasdos Rhabdas. It is also shown that this work is preserved as an autograph.